1998
DOI: 10.1152/jn.1998.80.3.1277
|View full text |Cite
|
Sign up to set email alerts
|

Orphanin FQ/Nociceptin Inhibits Synaptic Transmission and Long-Term Potentiation in Rat Dentate Gyrus Through Postsynaptic Mechanisms

Abstract: Orphanin FQ/nociceptin (OFQ), a recently characterized natural ligand for the opioid receptor-like 1 (ORL1) receptor, shares structural similarity to the endogenous opioids. Our previous study found that OFQ, like classical opioids, modulated synaptic transmission and long-term potentiation (LTP) in the hippocampal CA1 region, suggesting a modulatory role for OFQ in synaptic plasticity involved in learning and memory. In the present study we investigated the action of OFQ in the dentate gyrus and explored poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 25 publications
3
43
1
1
Order By: Relevance
“…NOP receptors are also located on interneurons and pyramidal cells throughout the hippocampus (Houtani et al, 2000), and can therefore directly modulate NMDA receptor function at the postsynaptic level. Consistent with this view, electrophysiological studies showed that exogenous as well as endogenous N/OFQ potently inhibits NMDA receptor-dependent long-term potentiation through direct action on pyramidal and granule cells in the hippocampus (Yu and Xie, 1998;Bongsebandhu-phubhakdi and Manabe, 2007). NOP receptor is a G-protein-coupled receptor that negatively regulates the activity of adenylate cyclases, inhibits voltage-gated Ca 2Ï© channels and activates inward rectifying K Ï© channels.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…NOP receptors are also located on interneurons and pyramidal cells throughout the hippocampus (Houtani et al, 2000), and can therefore directly modulate NMDA receptor function at the postsynaptic level. Consistent with this view, electrophysiological studies showed that exogenous as well as endogenous N/OFQ potently inhibits NMDA receptor-dependent long-term potentiation through direct action on pyramidal and granule cells in the hippocampus (Yu and Xie, 1998;Bongsebandhu-phubhakdi and Manabe, 2007). NOP receptor is a G-protein-coupled receptor that negatively regulates the activity of adenylate cyclases, inhibits voltage-gated Ca 2Ï© channels and activates inward rectifying K Ï© channels.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, NOP receptor activation with N/OFQ or synthetic agonists impairs memory performances in a variety of cognitive tasks in rodents (Sandin et al, 1997;Hiramatsu and Inoue, 1999;Redrobe et al, 2000;Higgins et al, 2002;Mamiya et al, 2003;Liu et al, 2007;Roozendaal et al, 2007), whereas the deletion of NOP receptor or preproN/OFQ gene produces the opposite effects (Manabe et al, 1998;Higgins et al, 2002;Mamiya et al, 2003). Consistent with these findings, electrophysiological studies showed that N/OFQ potently inhibits synaptic transmission and synaptic plasticity in the hippocampus and the amygdala (Yu et al, 1997;Meis and Pape, 1998;Yu and Xie, 1998;Wei and Xie, 1999; Bongsebandhu-phubhakdi and Manabe, 2007).…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…In addition, electrophysiological studies have demonstrated that OP 4 /nociceptin receptors can couple to inwardly rectifying K + channels in hippocampal preparations, and that nociceptin induces the activation of such channels (Ikeda et al, 1997). Furthermore, nociceptin inhibited synaptic transmission and synaptic plasticity such as long-term potentiation (LTP) in the rat hippocampus and dentate gyrus (Yu et al, 1997;Yu & Xie, 1998). [Nphe 1 ]-Nociceptin (1-13)-NH 2 , by blocking nociceptin receptors, may prevent such agonist-induced e ects and hence antagonize nociceptin-induced impairments of learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…At the cellular level, nociceptin acts at NOR to augment K + conductances in amygdalar (Meis andPape 1998, 2001), hippocampal (Amano et al 2000;Ikeda et al 1997;Madamba et al 1999;Tallent et al 2001;Yu and Xie 1998) and thalamic neurons (Meis 2003;Meis et al 2002), thus depressing cell excitability. Nociceptin has also been shown to decrease Ca 2+ currents (Abdulla and Smith 1997;Calo et al 2000;Connor et al 1999;Henderson and McKnight 1997;Larsson et al 2000) and reduce the amplitude of both non-NMDA receptor-mediated excitatory postsynaptic currents (EPSCs) and IPSCs in rat lateral amygdala (Meis et al 2002).…”
Section: Neuropeptide Y-neuropeptide Y (Npy)mentioning
confidence: 99%